Global λ-Stability of One Nonautonomous Quasilinear Second-Order Equation - Vitrychenko, I. E. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish sufficient conditions for the λ-stability of the trivial solution of one quasilinear differential equation of the second order.